Automatic Drought Tolerance Measurement of the Soil-Living Microarthropod, Folsomia Candida - Sipőcz, László; Ittzés, András; Dombos, Miklós (Journal of Environmental Geography, 2023)
Soil is a complex habitat where microarthropods, such as mites (Acari) and springtails (Collembola) species occur in high number and species diversity. Microarthropods play an essential role in organic matter decomposition and provide an important ecosystem service in soil. The soil-dwelling microarthropods are sensitive to environmental changes; therefore, their ecological characteristics are used to evaluate soil conditions. In modern environmental ecology, several species are involved in assessing the ecological consequences of drought periods. The growth rate is a standard sublethal parameter by which the body size of individuals is measured. Extracting microarthropods from the soil is difficult and time-consuming, requiring a high amount of human resources. Only a few samples can be processed due to laboratory limitations and high costs. However, nowadays the rapidly developing artificial intelligence (AI) technologies promise new opportunities in many research areas. Data on soil-dwelling microarthropods could be collected quickly and automatically using our new digital soil extractor device, the Edapholog, equipped with image analysis based on AI. This device recognizes living individuals, classifies them, and measures their body length automatically. Using this system, the growth and reproductive success of various species in the same experimental culture could be rapidly and simultaneously monitored. In this study, we aimed to analyse the applicability of the Edapholog for measuring the body size of Collembola species and Folsomia candida through a set of drought tolerance tests with three soil moisture treatment levels. Moisture content was set based on the maximum water holding capacity (Wmax) of the soil applied. The three levels were set to Wmax:35%, 40%, and 50%. Furthermore, we aimed to test the reliability of the detection and recognition of the species and the accuracy and reliability of the automatic body size measurement of individuals. Significant correlation (r= 0.94) exists between the automatically and manually measured body sizes. Although the different soil moisture treatments did not show marked differences in the collembolan body sizes between the moisture treatments, we found a significant difference in the reproduction rates between W50 and the other two (W35 and W40) treated groups. The Edapholog can greatly contribute to quick and precise data extraction and can have vast applicability in environmental ecology.